2022
DOI: 10.1038/s41598-022-22874-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse width and intensity effects of pulsed electric fields on cancerous and normal skin cells

Abstract: Microsecond pulsed electric fields (PEF) have previously been used for various tumour therapies, such as gene therapy, electrochemotherapy and irreversible electroporation (IRE), due to its demonstrated ability. However, recently nanosecond pulsed electric fields (nsPEF) have also been used as a potential tumor therapy via inducing cell apoptosis or immunogenic cell death to prevent recurrence and metastasis by interacting with intracellular organelles. A large proportion of the existing in-vitro studies of ns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…As shown by Rao et al in 2022, cellular response is higly influenced by the parameters of the magnetic field, like the pulse width. Also small modifications of this parameter, from nanoseconds to milliseconds 35 , were associated with different patterns of intracellular compartments, and consequently, to different biological effects. The effects of CMFs on fibroblasts’s ROS production is dependent on the program applied, but also on the cellular status.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Rao et al in 2022, cellular response is higly influenced by the parameters of the magnetic field, like the pulse width. Also small modifications of this parameter, from nanoseconds to milliseconds 35 , were associated with different patterns of intracellular compartments, and consequently, to different biological effects. The effects of CMFs on fibroblasts’s ROS production is dependent on the program applied, but also on the cellular status.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation studies further shown that very short nsPEF (30 ns) induces differential response in a between cancerous and normal cells based on the differences in the morphological features as well as the pattern of potential difference assembled on the nucleoplasm and cytoplasm. The simulation data was further veri ed with in-vitro work on B16 cells and L929 cells [33]. In order to improve the desired prognosis while minimising side effects, it is crucial to take into account the selective sensitivity of normal and malignant cells to nsPEF.…”
Section: Discussionmentioning
confidence: 99%
“…A pulsed electric field with nanosecond-level pulse width can create significantly smaller pores on the cytomembrane compared to those observed with microsecond-range electroporation, which only permits the passage of small molecules like ions [ 216 ]. Hence, some biological effects, such as cell apoptosis induced by electroporation, can only be triggered by EStim with definite wave width [ 217 ]. In summary, despite a number of clinical research revealed the significance of parameters of pulsed EStim, the underline mechanisms still require more investigations before complete emerging.…”
Section: Exogenous Electric Stimulationmentioning
confidence: 99%